Water productivity : principles and practices - Umesh, M. R.; Chittapur, B. M. (Daya Publishing House, 2021)
This book is a comprehensive knowledge source to the researchers, teaching faculty, students and other agriculture professionals. Not only importance of water is highlighted as a precious non-renewable natural resource but also the on-farm water management is equally emphasized considering the high water requiring crops as well as most efficient irrigation systems and practices with necessary work sheets. It is hoped that the book serves as a reference source for graduate and post graduate students and faculty in agricultural universities in India and abroad. This book is comprised of 32 chapters prepared on variety of topics by eminent personalities involved in agriculture research, education and extension. Previous exercises made in the country and elsewhere are briefed and new trends in water management are delineated in these chapters. Overall, the issues covered in the book are of practical and policy significance with detailed deliberations which often reappear because of their importance and diversity of experts.